Implementation of Open-Ended Approach to Improve Mathematical Creative Thinking Skills and Self-Efficacy - Ihwana, Mirna; Putra, Harry Dwi; Sumarmo, Utari (IKIP Siliwangi, 2025)
This study looks at mathematical thinking and self-efficacy, which is a wonderful idea because everyone needs to be innovative and creative to keep up with technology advancements in the age of society 5.0. Additionally, each student's self-efficacy may rise as a result. The study employed quantitative methodologies, with a sample size of thirty individuals for both the experimental and control groups. The researchers developed two instruments to facilitate the measurement of abilities. One of the instruments is a test with questions that are intended to assess the creative mathematical thinking skills of the subjects, including Agility (flexibility), Authenticity (originality), and Details (elaboration). Based on the study's findings, it can be concluded that the research findings indicate that students taught mathematics through the Open-Ended approach demonstrated a higher level of development of creative mathematical thinking skills compared to those taught through traditional approaches. end up outperforming others who were educated utilizing conventional approaches. The research discussion results revealed that students who were taught mathematics using an Open-Ended approach demonstrated a greater development in creative mathematical thinking abilities than those who were taught using a conventional method. This conclusion was reached based on the research findings and the debate that followed. completed the task more successfully than those instructed using conventional ways. The study's results and the discussion that followed led to the conclusion that, in terms of developing students' potential for mathematical creativity, there was no connection between the learning technique and students' baseline mathematical proficiency. There is no correlation between beginning mathematical competency and learning methodologies and increasing pupils' self-efficacy, according to research and discussion.